Evaluating the quality of fed funds lending estimates produced from fedwire payments data - Anna Kovner; David Skeie (Federal Reserve Bank of New York, 2013)
A number of empirical analyses of interbank lending rely on indirect inferences from individual interbank transactions extracted from payments data using algorithms. In this paper, we conduct an evaluation to assess the ability of identifying overnight U.S. fed funds activity from Fedwire® payments data. We find evidence that the estimates extracted from the data are statistically significantly correlated with banks' fed funds borrowing as reported on the FRY-9C. We find similar associations for fed funds lending, although the correlations are lower. To be conservative, we believe that the estimates are best interpreted as measures of overnight interbank activity rather than fed funds activity specifically. We also compare the estimates provided by Armantier and Copeland (2012) to the Y-9C fed funds amounts.
Keywords: G21; C81; E40; 330; federal funds market; data quality; interbank loans; fed funds; Fedwire; Y-9C